Assessments of physical, social, and economic vulnerability in Tarakan due to climate change - Pratiwi, Sulistya Rini; Nainggolan, Yohanna Thresia; Utomo, Mohamad Nur (Jurnal Ekonomi dan Bisnis, 2024)
Climate change is one of the phenomena that affects the condition of coastal communities in their physical, social, and economic aspects. Communities in a coastal area are considered vulnerable because they live in a disaster-prone area. This study aims to examine the classification of physical, social, and economic vulnerability as well as the capacity of coastal communities due to climate change in Tarakan City and to measure the relationship between physical, social, and economic vulnerability and community capacity from disasters due to climate change in Tarakan City. The data used are qualitative and quantitative, with a descriptive approach using the Likert scale method, the Guttman scale, the rating scale, and the Spearman rank correlation test. The results demonstrate that the level of physical vulnerability of the coastal community in Tarakan City was high at 80%, and the socioeconomic vulnerability of the coastal community in Tarakan City was medium at 52% and 52%, respectively. Meanwhile, the level of community capacity is high at 69%. The level of relationship between physical, social, and economic vulnerability and community capacity is very weak.